Evaluasi Penerapan Prosedur Operasional Standar Pengelolaan Keuangan Daerah di Provinsi Papua - Yemima Eka Christy; Elisabeth Penti Kurniawati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
Implementation of Standard Operating Procedures (SOP) in the regional financial management should be conducted based on an internal control system in the local government. When conducting the examination, BPK shall examine and assess the internal control system of the local government. Thus, if the internal control system of the local government is adequate, then compliance toward SOP can be implemented, and the results of the testing and examination of BPK is expected to give a favorable opinion. The provincial government of Papua has decreased the results of the examination of financial statements for three consecutive years. In 2007-2009 the provincial government of Papua gets a qualified opinion, and in 2010 received a disclaimer opinion. The purpose of this study was to evaluate SOP application compliance of regional financial management, which can be known to through BPK examination report containing the findings and their opinions based on the criteria. The results showed that theProvincial Government of Papua has prepared SOP of its financial management in line with the rule in force. However, the SOP is not fully adhered to in practice, due to several factors: (1) weak of government internal control systems;(2) lack of financial management guidance and supervision.